Groups as units of functional analysis, individuals as proximate mechanisms. Issue 3 (27th June 2014) - Wilson, David Sloan
Abstract Whenever selection operates at a given level of a multitier hierarchy, units at that level should become the object of functional analysis, and units at lower levels should be studied as proximate mechanisms. This intuition already exists for the study of genes in individuals, when individuals are the unit of selection. It is only beginning to be applied for the study of individuals in groups, when groups are the unit of selection. Smaldino's target article is an important step in this direction with an emphasis on human cultural evolution, but the same algorithm applies to all multilevel evolutionary processes.